The Transgender Nation and its Margins: The Many Lives of the Law - Sayan Bhattacharya (South Asia Multidisciplinary Academic Journal, 2019)
In a 2014 judgment, the Supreme Court of India affirmed the right of every Indian citizen to choose their gender identity regardless of gender affirmation surgery. Following this judgment, states across India have been constituting transgender welfare boards and the Indian government has approved the Transgender Persons’ (Protection of Rights) Bill, 2018 that is supposed to be the one law that will safeguard transgender individuals from any form of discrimination. This legal recognition also coincides with a series of media campaigns that depict transgender individuals staking their claim to Indian citizenship through the trope of nationalism, which is always already majoritarian Hindu nationalism. Thus, these twin developments raise the question of whether performing Hindu nationalism is the only way to claim Indian citizenship. Recent queer studies scholarship from India warns us of the danger of queer and transgender movements getting folded into majoritarian Hindu nationalism, creating constitutive outsides comprised of non-citizens who cannot perform such nationalism. This paper argues that such a meta-narrative risks the danger of missing out on the micro-narratives of resistance and protests emerging from within India’s transgender movements that disrupt any singular narrative of transgender individuals performing nationalism to seek citizenship rights.